Effects of Problem-Based Learning and Interactive Invention Instructional Strategies on NCE Pre-Service Teachers’ Achievement in Physics Concepts and Acquisition of Science Process Skills (2012)
The traditional instructional strategies employed by most physics teachers in teaching the subject has consistently led to low student achievement. Hence there is need to employ new instructional strategies such as problem-based learning (PBL) and inter-active invention (IIS) instructional strategies, particularly, among the NCE pre-service teachers in Nigeria. The two strategies have been proved in the literature to help in alleviating the problem of low student achievement in physics, but they have not been adopted in the teaching of physics in Nigerian Colleges of Education. This study, therefore, ascertained the effects of problem–based learning and interactive invention instructional strategies on NCE pre-service teachers‘ achievement in physics and acquisition of science process skills. A pretest-posttest, control-group, quasi–experimental research design with a 3x3x2 factorial matrix was used. Three state and three federal colleges of education from South-western Nigeria were purposively selected. Ninety eight female and 94 male final year NCE physics students with high, medium and low self-efficacy constituted the sample. One state and one federal college of Education were used for each of the two experimental groups and the control group. The Instruments used were: Physics Achievement Test (r=0.875), Students‘ Physics Self–Efficacy Questionnaire (r=0.956), Science Proces Skills Worksheets (SPSW), Classroom Activities Rating Scale (r=0.820), Teachers‘ Instructional Guides for Problem-Based Learning Strategy (PBLS), Interactive Invention Strategy (IIS) and Conventional Lecture Method (CLM). Three research questions were answered and seven null hypotheses were tested at 0.05 level of significance. Data were analysed using Analysis of Covariance (ANCOVA), Multiple Clasification Analysis (MCA) and Scheffe post hoc analysis. Treatment had a significant main effect on pre-service teachers’ achievement in physics concepts (F(2,174) = 43.44, P <.05) and science process skills acquisition (F(2,175) = 183.80, P <.05). In achievement in physics concepts, students exposed to problem-based learning obtained a higher achievement score (=51.98) than those exposed to interactive invention instructional strategy ( =40.32) and the conventional lec-ture method ( =30.23). Those exposed to problem-based learning instructional strategy obtained higher science process skills scores ( =73.67) than those exposed to interactive invention instructional strategy (=60.21) and conventional lecture method (=26.73). There was no significant main effect of gender on pre-service teachers’ achievement in physics (F (1 174) = .026 P > .05) and acquisition of science process skills (F (1,175) = .361, P >.05). The three-way interactions of treatment, self-efficacy and gender showed a significant interaction effect for achievement in physics (F (3,174) = 3.27, P<.05) and for science process skills acquisition (F(3,175) = 2.92, P <.05). There was no significant effect of self-efficacy and gender on achievement and science process skills acquisition; the two-way interactions showed no significant effect. Problem–based learning and interactive invention instructional strategies improved student achievement in physics and science process skills acquisition. It is, therefore, recommended that teachers, curriculum developers and textbook writers should adopt these two instructional strategies for the improvement of students‘ learning outcomes in physics.